AB0780 Identification of Knee OA Phenotypes: A Replication Study Using Data from the Amsterdam Osteoarthritis Cohort. (10th June 2014) - Knoop, J.; van der Esch, M.; Roorda, L.D.; van der Leeden, M.; Knol, D.L.; Lems, W.F.; Dekker, J.
Abstract : Background: We previously identified 5 clinically relevant phenotypes from a heterogeneous knee OA population (Osteoarthritis Initiative [OAI] cohort), which needs to be replicated for validation. Objectives: The present study aims to replicate this phenotype identification for validation in a clinical setting using data from the Amsterdam Osteoarthritis (AMS-OA) cohort. Methods: K-means clustering analysis was performed in 374 knee OA patients from the AMS-OA cohort, using 4 clinically relevant and easily obtainable patient characteristics or clustering variables: radiographic severity (Kellgren/Lawrence [K/L] grade), body mass index (BMI), upper leg muscle strength, and depression (from Hospital Anxiety and Depression Scale [HADS] questionnaire). The cluster solution with the highest Pseudo F value was considered the most adequate number of clusters or phenotypes in the dataset. This solution was compared with the original study. Results: The most adequate number of phenotypes was 5, similar as in the original study. Moreover, the 5 identified phenotypes represented in general similar phenotypes compared to the original study, namely a "minimal joint disease phenotype", a "strong muscle phenotype", a "non-obese weak muscle phenotype" (although obesity was more prevalent compared to the original study), an "obese weak muscle phenotype", and a "depressive phenotype" (although depression was less prevalent compared to the original study). Conclusions: The identification of phenotypes from the OAI cohort could be replicated, except for two minor differences that are presumably attributable to differences in study population. The phenotype identification seems therefore a valid finding, with phenotypes possibly representing different etiological subtypes of knee OA in which phenotype-specific interventions may be needed. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3277